1998
DOI: 10.1073/pnas.95.26.15299
|View full text |Cite|
|
Sign up to set email alerts
|

High-resolution NMR of encapsulated proteins dissolved in low-viscosity fluids

Abstract: The majority of known proteins are too large to be comprehensively examined by solution NMR methods, primarily because they tumble too slowly in solution. Here we introduce an approach to making the NMR relaxation properties of large proteins amenable to modern solution NMR techniques. The encapsulation of a protein in a reverse micelle dissolved in a low-viscosity fluid allows it to tumble as fast as a much smaller protein. The approach is demonstrated and validated with the protein ubiquitin encapsulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
167
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(170 citation statements)
references
References 33 publications
3
167
0
Order By: Relevance
“…Furthermore, the Stokes-Einstein equation [Eq. (4)] demonstrates that the tumbling time of an isotropically reorientating (spherical) molecule is linearly related to the bulk solvent viscosity: [25] …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Stokes-Einstein equation [Eq. (4)] demonstrates that the tumbling time of an isotropically reorientating (spherical) molecule is linearly related to the bulk solvent viscosity: [25] …”
Section: Discussionmentioning
confidence: 99%
“…The increases of effective molecular size and bulk solvent viscosity can both contribute to the global change in relaxation parameters (33). Therefore, PFG-NMR diffusion experiments were used to discriminate between those.…”
Section: Substantial Chemical Shift Changes Indicate a Strong Dependementioning
confidence: 99%
“…In these experiments the AOT RMs are dissolved in low-viscosity solvent, in order to increase the tumbling speed of the confined protein. 24,25 Proof-of-principle studies have shown that the structure of ubiquitin does not change significantly upon encapsulation, although there are some changes in the dynamics.…”
mentioning
confidence: 99%